Associations between SARS-CoV-2 infection and incidence of new chronic condition diagnoses: a systematic review. Issue 1 (31st December 2023) - Gaudet, Lindsay A.; Pillay, Jennifer; Saba, Sabrina; Zakaria, Dianne; Cheta, Nicholas; Gardiner, Hélène; Shaver, Larry; Middleton, Jacqueline; Tan, Maria; Vandermeer, Ben; Hartling, Lisa
ABSTRACT: Because of the large number of infected individuals, an estimate of the future burdens of the long-term consequences of SARS-CoV-2 infection is needed. This systematic review examined associations between SARS-CoV-2 infection and incidence of categories of and selected chronic conditions, by age and severity of infection (inpatient vs. outpatient/mixed care). MEDLINE and EMBASE were searched (1 January 2020 to 4 October 2022) and reference lists scanned. We included observational studies from high-income OECD countries with a control group adjusting for sex and comorbidities. Identified records underwent a two-stage screening process. Two reviewers screened 50% of titles/abstracts, after which DistillerAI acted as second reviewer. Two reviewers then screened the full texts of stage one selections. One reviewer extracted data and assessed risk of bias; results were verified by another. Random-effects meta-analysis estimated pooled hazard ratios (HR). GRADE assessed certainty of the evidence. Twenty-five studies were included. Among the outpatient/mixed SARS-CoV-2 care group, there is high certainty of a small-to-moderate increase (i.e. HR 1.26–1.99) among adults ≥65 years of any cardiovascular condition, and of little-to-no difference (i.e. HR 0.75–1.25) in anxiety disorders for individuals <18, 18–64, and ≥65 years old. Among 18–64 and ≥65 year-olds receiving outpatient/mixed care there are probably (moderate certainty) large increases (i.e. HR ≥2.0) in encephalopathy, interstitial lung disease, and respiratory failure. After SARS-CoV-2 infection, there is probably an increased risk of diagnoses for some chronic conditions; whether the magnitude of risk will remain stable into the future is uncertain.